ANSI/ISO C++ professional programmer's handbook - Kalev, Danny (Que, 1999)
The ANSI/ISO C++ Professional Programmers Handbook is a concise professional C++ reference tool that presents all of the changes and addenda to the language specification. It contains tips and guidelines for exerting the full potential of C++ as a multi-purpose object-oriented programming language. The new Standard Briefing component provides coverage of the latest version of the C++ language including additions and modifications to the language, new constructs such as built-in bool type, namespaces, RTTI, new header file conventions, internalization, memory management and new cast notation. Additionally, we've included a Manual of Programming Style, a Compatibility Compendium, and Future Directions overview.